Assessment of Indoor Household Air Quality Using SentinAir's Cost-effective Sensor - Abulude , Francis Olawale; Oluwafemi, Matthew Ojo; Arifalo, Kikelomo Mabinuola; Elisha, Jamok Jacob; Kenni, Amoke Monisola (Tropical Aquatic and Soil Pollution, 2023)
According to the World Health Organization, particulate matter (2.5 m) is responsible for more than 4 million deaths worldwide. In real-time, low-cost sensors have assisted in the measurement of PM indoors. SentiAir, a low-cost instrument used in this study, monitors particulate matter (1, 2.5, and 10), as well as nitrogen dioxide, sulphur dioxide, carbon dioxide, ozone, temperature, and relative humidity. The goal of this study was to place the sensor in a typical household indoor space and evaluate all variables for 30 days as an initial investigation assessment. The sensor's proper procedure was strictly observed. PM1 (17.80 μg/m3), PM2.5 (25.21 μg/m3), PM10 (27.61 μg/m3), CO2 (419.7 ppm), O3 (24.75 ppb), NO2 (66.52 ppb), SO2 (48.04 ppb), temperature (34.1 °C), and humidity were the results (mean) (64%). Once those findings were compared to those of the WHO, it was discovered that PM2.5 and PM10 were well within the 24-hour guideline values of 25 and 50 μg/m3, respectively. However, PM2.5 may pose a risk. Temperature and humidity had a significant impact on the PM and gases. Cooking, especially frying and baking, produced a great increment in PM indoors.